Preparation Of Natural Rubber/High Density Polyethylene Composite Reinforced Rice Husk Treated With Liquid Epoxidized Natural Rubber (LENR) - Rahmadini Syafri; Prof Dr. Ibrahim Abdullah; Prof Madya Dr. Ishak Ahmad (Jurnal Zarah, 2013)
Thermoplastic natural rubber (TPNR) composites with rice husk (RH) as filler were prepared via melt blending using an internal mixer Brabender Plasticorder. TPNR matrix was prepared from natural rubber (NR) and high density polyethylene (HDPE) with a composition ratio of 60:40. The optimum processing parameters for NR/HDPE matrix was obtained at 135 oC, at mixing rate of 50 rpm and blending time of 12 minutes, while the parameters for the NR/HDPE/RH composite was at 135 oC mixing rate of 45 rpm and blending time of 12 minute. Addition of rice husk into the NR/HDPE matrix was aimed to reinforce the composites with the filler. The high silica content of rice husk has made rice husk to be used as potential reinforcement filler for composites. However, the application of rice husk as filler is limited due to the hydrophilic nature of rice husk surface causing incompatibility and weak interfacial adhesion between rice husk and the hydrophobic polymer matrix. Hence, the cellulose surface of rice husk has to be modified. The rice husk was treated with sodium hydroxide (NaOH) as pre-treatment and later coated with liquid epoxidized natural rubber (LENR). Several concentrations of NaOH solution were used for alkali treatment of untreated rice husk (RHi) and the most effective was at 5% NaOH in aqueous solution (RHiNa). LENR coating was also carried out at several concentrations from 5% to 20% LENR in toluene. Characterizations of rice husk surfaces were analyzed by FTIR, optical microscope and SEM micrograph. The mechanical properties of rice husk filled composites observed, showed that the maximum value obtained were for composites reinforced with alkali treated and coated with 10% of LENR (RHiNaLE 2). The tensile and impact strength obtained were 6.9 MPa and 24.6 kJ/m2 respectively. Effects of RHiNaLE 2 loading on tensile and impact strengths of composites showed that the properties decreased at higher loadings due to agglomeration of filler particles. However the tensile modulus and hardness were found to increase with filler loading. The dynamic mechanical thermal analysis also showed that composites prepared exhibited a shift in the tan delta peak (Tg) to a higher temperature due to the increased RHiNaLE 2-Matrix interaction. In conclusion, modification of rice husk surface via NaOH treatment and coating with LENR was successful in reducing the hydrophilic nature of rice husk powder. The RHi-Matrix interfacial adhesion had improved which lead to higher mechanical properties of the composites prepared.